(untitled) (Research, Society and Development, 2021)
Considering the public health emergency character of the pandemic; the urgency to adjust and rethink nursing care, with a view to overcoming or minimizing the clinical problems of people affected by Covid-19; and the importance of nurses’ clinical decision-making in a quick, efficient and safe way, the objective was to develop an Android OS application capable of supporting the clinical reasoning of nurses, based on the steps of the nursing process for patients affected by COVID- 19. Methodological study, using the PMBOK for application development, following the steps organized into five groups of processes: 1. Initiation; 2. Planning; 3. Execution; 4. Monitoring; and 5. Closing. The development of the application project took place between the months of May and June 2020. The results and discussions show, at each stage, the feasibility of the application development, necessary resources and definition of the operating supporting system; the scope of the application was defined in order to enable the chain of ideas about nursing care; and the execution of activities necessary to achieve the project’s objectives; performance monitoring strategies. It is concluded that the objective was fulfilled and that the authors’ knowledge about Nursing information system programming and know-how was essential for the creation and projection of the Nursing COVID-19 application, in a fast time as required by the emergence of the pandemic and according to the needs of nurses.